Iron thunder : the battle between the Monitor & the Merrimac : a Civil War novel - Avi, 1937- (Hyperion Books for Children, Scholastic, 2007)
Thirteen-year-old Tom Carroll takes his place as head of the family after his father dies fighting for the Union; but his job at the local ironworks, where he helps build an iron ship for the Union army, and his loyalty come into question when he is approached by Confederate spies to sell secrets about the ship to the South.